WACANA PADANAN ISTILAH ASING-INDONESIA DAN KAITANNYA DENGAN PEMBELAJARAN BAHASA INDONESIA BAGI PENUTUR ASING (BIPA) - Sudaryanto, Sudaryanto; Hermanto, Hermanto; Wijayanti, Dedi (JURNAL PESONA, 2018)
Indonesian continues to experience the addition of foreign equivalent vocabulary, especially from English. It is anticipated by the Agency for Language Development or Language Development or its technical implementation unit (UPT), Balai Bahasa or Kantor Bahasa, by publishing a number of infographics in three sections, such as âKata Kita Pekan Iniâ, âPadanan Istilahâ, and âIstilah Hari Iniâ. All three became the equivalent of foreign-Indonesian discourse. This study uses content analysis techniques to the data in the form of discourse matched foreign-Indonesian terms. The validity of data in qualitative research is done with two concepts, namely the concept of validity and the concept of reliability. The result of the research shows that the foreign-Indonesian equivalent discourse can be used as instructional material in learning Indonesian for foreign speakers (BIPA), as well as a supporting tool in Indonesian language preaching.